The role of religious spirituality and work engagement on job performance - Zahrah, Novia; Aziz, Azelin; Abdul Hamid, Siti Norasyikin (UUM College of Business, 2018)
This paper conceptualizes the role of work engagement as mediation on the relationship between religious spirituality and job performance of Muslim employees in Malaysia.Religious spirituality involves the belief in the existence of God and the power of prayer as a way of communicating with God in all aspects of life. Religious spirituality encourages individuals to mends the relationship between God and human (hablu minallah) as well as the relationship between human beings (hablu minannas) in order to be able to deal with hardship and obtains long-term satisfaction. The ability of an employee to overcome any hardship will enhance their work engagement and job performance. Thus, in response to the impact of religious spirituality in enhancing work engagement and job performance, this study develop several propositions that demonstrate the significant role of related variables in enhancing job performance. Suggestions for future research and implications of the study for managers are presented. This study recommends management and human resource practitioners to be proactive and formulate preventive strategy against low productivity among Muslim employees by provides training, create an environment that supports wholeness, meaningful work, and feeling of inner satisfaction. However, there is need for empirical studies to test the proposed relationships.